PENGARUH PREMANAGED EARNINGS DAN DIVIDEN YANG DIHARAPKAN TERHADAP PRAKTIK MANAJEMEN LABA - Wibiksono, Rosalia Anita; Rudiawarni, Felizia Arni (UI Scholars Hub, 2015)
This study aims to determine whether the companies paying dividend in the previous year (payers) are more likely to perform earnings management than companies that do not (non-payers) in order to meet the expected dividend. The study also examines the impact of premanaged earnings and expected dividend on earnings management practices. Sample used in this research are manufacturing companies listed in Indonesia Stock Exchange in 2010-2012. The findings suggest that there is a significant negative relationship between premanaged earnings and discretionary accruals, and a significant positive relationship between the expected dividends and discretionary accruals. This study concludes that dividend is important determinant of earnings thresholds. However, dividend is not a unique motivation to perform earnings management.